Writings on Silesia: A Selection (2024) (Zaranie Śląskie, 2025)
This list presents selected descriptions of monographic publications related to Upper Silesia, the Opole region, and Cieszyn Silesia, as well as the Dąbrowa Basin and the Częstochowa region. Further information, including descriptions of articles from academic and popular journals as well as from the press, is available in the Regional Bibliography database of the Silesian Library in Katowice (bibliografia.bs.katowice.pl).
Keywords: regional bibliography; Upper Silesia; Cieszyn Silesia; the Dąbrowa Basin; the Częstochowa region